History of Studies Toward Control and Eradication of Bovine Tuberculosis in Turkey - Yüksel, Özlem; Özen, Abdullah (Sivas Cumhuriyet Üniversitesi, 2021)
[EN] Tuberculosis has been known to cause deaths in humans and animals since ancient times. This disease has almost been eliminated with the control and eradication studies which have been practiced in many European and new world countries from past to present. This study aimed to examine and evaluate all stages of the studies carried out on the control and eradication of bovine tuberculosis disease, starting from the oldest available sources, in the historical process, and thus to provide data for fighting strategies in general and control and eradication studies in particular. In Turkish history, although some strategies were aimed to be created from time to time within the scope of the fight against tuberculosis, the fight against the disease has become effective in the period after the proclamation of the Republic. The first drilling study on tuberculosis was launched in 1929 and the second one was in 1938. The first national-scale control study was the "Turkish Fight Against Tuberculosis Project", which was prepared in 1985. Some of the 19th century regulations enacted within the scope of combating epidemic animal diseases during the Ottoman Empire also included the fight against bovine tuberculosis. However, the first regulation to be issued independently within the scope of combating this disease was the "Regulation on Bovine Tuberculosis " which came into force in 1932. Following this directive, five more regulations were introduced regarding bovine tuberculosis. Consequently, as a result of the studies carried out on the fight against bovine tuberculosis, which causes disease in both animals and humans and poses a danger to public health, it can be argued that a fluctuating success curve has been achieved in the fight against tuberculosis and the desired level of success has not been achieved in general.

Tüberküloz, çok eski çağlardan beri bilinen, günümüze kadar insan ve hayvanlarda ölümlere neden olmuş bir hastalıktır. Geçmişten günümüze kadar birçok Avrupa ve yenidünya ülkesinde yapılan kontrol ve eradikasyon çalışmaları ile hastalık neredeyse tamamen ortadan kaldırılmıştır. Bu çalışmada, ulaşılabilen en eski kaynaklardan başlayarak, sığır tüberkülozu ve bu hastalığın kontrolü ve eradikasyonuna yönelik çalışmaların tüm aşamalarının tarihsel süreçte incelenmesi, değerlendirilmesi ve bu sayede, genelde mücadele stratejilerine, özelde ise kontrol ve eradikasyon çalışmalarına veri sağlanması amaçlanmıştır. Türk tarihinde, tüberkülozla mücadele kapsamında dönem dönem bazı stratejiler oluşturulmaya çalışılmışsa da hastalıkla mücadele Cumhuriyetin ilânından sonraki süreçte etkin bir hâl kazanmıştır. Tüberkülozla ilgili ilk sondaj çalışması 1929; ikincisi ise 1938 yılında başlatılmıştır. Ülkesel ölçekli ilk mücadele çalışması ise 1985 yılında hazırlanan “Türkiye Tuberculosis Mücadele Projesi”dir. Osmanlı Devleti döneminde salgın hayvan hastalıklarıyla mücadele kapsamında çıkarılan 19’uncu yüzyıla ait bazı düzenlemeler sığır tüberkülozu mücadelesini de kapsamıştır. Ancak bu hastalıkla mücadele kapsamında müstakil olarak çıkarlan ilk düzenleme 1932 yılında yürürlüğe girmiş olan “Sığır Tüberkülozu Talimatnamesi”dir. Bu talimatnameyi takiben sığır tüberkülozu ile ilgili beş ayrı düzenleme daha yapılmıştır. Sonuç olarak gerek hayvanlarda ve gerekse insanlarda hastalığa neden olan ve halk sağlığı açısından tehlike arz eden sığır tüberkülozuyla mücadele konusunda yürütülen çalışmalar neticesinde, tüberkülozla mücadelede inişli-çıkışlı bir başarı eğrisi elde edilmiş olmakla beraber, genel olarak istenen başarı düzeyine ulaşılamadığı ileri sürülebilir.
Türkiye’de Sığır Tüberkülozunun Kontrolü ve Eradikasyonuna Yönelik Çalışmaların Tarihi
Keywords: Veterinary Surgery; Veteriner Cerrahi